Pentacene organic thin‐film transistor with HfYO gate dielectric made on adhesive vacuum tape. Issue 8 (1st April 2015) - Han, C.Y.; Tang, W.M.; Leung, C.H.; Lai, P.T.
Abstract : Pentacene organic thin‐film transistor (OTFT) with HfYO as gate dielectric has been fabricated at room temperature on adhesive flexible vacuum tape and shows high performance. The threshold voltage is as low as −1.77 V due to the high‐ κ gate dielectric employed. A small sub‐threshold swing (SS) of 0.145 V/dec indicates good interface between the gate dielectric and pentacene film. Atomic force microscopy (AFM) reveals that large pentacene gains form on the HfYO gate dielectric, leading to a high carrier mobility of 0.236 cm 2 V −1 s −1 . These good results suggest that the adhesive vacuum tape can be used as the substrate for adhesive flexible OTFT, and HfYO is a promising gate dielectric for high‐performance pentacene OTFT.